Answer:
i did.
Step-by-step explanation:
D. asymptote
In the attached graph, the function has two asymptotes, one horizontal (the x-axis) and one vertical (the line x = 2).
G(x) = (x-2)^3
move F(x) = x^2 to the right 2 units
answer
C. G(x) = (x-2)^3
Answer:
the length of all sides added together
Answer:
.
Step-by-step explanation:
a.) 72 ÷ 8 × 9 = 81 (we divide 72 by 8 first then multiply the result with 9)
b.) -72 ÷ 8 × 9 = -81 (it's same with a only differ by negative sign)
c.) 72 ÷ (-8) × 9 = -81 (dividing 72 by -8 will give us -9 and multiplying -9 by -9 will give the result of -81)
d.) 72 ÷ 8 × (-9) = -81 (divide 72 by 8 and it will be 9, mutliply it by -9 and again it will give -81)
e.) -72 ÷ 8 × (-9) = 81 (divide -72 by 8 and it will be -9 multiplying it by -9 will give a positive 81 since two negative signed numbers multiplied or divided gives positive result)